Merokok dan Vaping Sebagai Faktor Resiko Terjadinya Gangguan pada Hati - Mubarak, Raka Anzil; Windarti, Indri; Yunianto, Andi Eka (CV. Jasa Sukses Abadi, 2024)
Conventional cigarettes and e-cigarettes (vaping) has a significant impact to health issues worldwide. There are more than 1.1 billion active smokers in the world and 8 million people die each year due to tobacco consumption. E-cigarette use is also increasing. The liver is responsible for metabolism and detoxification, so it is highly vulnerable to the toxic effects of chemical compounds from conventional cigarettes and e-cigarettes. This article is a literature study using secondary data from articles in national and international journals sourced from Google Scholar, NCBI, and PubMed. The purpose of this article is to review the relation between smoking, vaping, and the risk of liver disease, with a focus on the components of cigarettes and the mechanisms of liver damage. There are 4000 chemicals contained in cigarettes, including nicotine which are addictives and stimulants. The effects of smoking on the liver are caused by toxic, immunologic, and oncogenic mechanisms. The use of e-cigarettes or vaping is gaining popularity as a safe alternative to conventional cigarettes. However, each e-liquid solution can contain up to 60 chemicals that are harmful to the body. The effects of e-cigarettes on the liver are explained by complex mechanisms such as oxidative stress, inflammation, mitochondrial dysfunction and impaired lipid metabolism in the liver. Smoking affects the progression of liver diseases such as Hepatitis, Non Alcoholic Fatty Liver Diseases (NAFLD), Primary Billier Cholangitis (PBC), and Hepatocellular carcinoma (HCC). Vaping has an association with the incidence of NAFLD and HCC, but there is not yet strong enough evidence to associate it with the progression of Hepatitis and PBC.